IMPLEMENTASI SIMPLE ADDITIVE WEIGHTING DALAM PENENTUAN BIBIT JAGUNG VARIETAS UNGGUL DI WILAYAH LAHAN LAHAN KERING - Bone, Leonardus; Kelen, Yoseph Pius Kurniawan; Ullu, Hevi Herlina; Gelu, Leonard Peter (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Corn is a staple food source that is rich in carbohydrates. As a source of carbohydrates, some people consume corn as daily food. Determination of corn seeds is an aspect that needs to be considered by farmers before planting because inaccurate selection of seeds can cause unsatisfactory yields and cause farmers to suffer losses. Determination of corn seeds carried out by farmers in Nansean Village and East Nansean Village is still using a manual method by looking at the size of the large fruit and choosing from seeds that have a fast harvest time but will produce unsatisfactory yields which causes farmers to feel crop failure. So it is necessary to build a decision support system that can provide answers to problems using the Simple Additive Weighting (SAW) method. The capability of the system built can provide solutions in selecting superior corn seeds for farmers and the results are in the form of rankings. The system development model used in developing this system is the waterfall model. Based on the research results, the chosen alternative in this study was alternative A01, namely NASA 29 Hybrid Corn with a total value of 0.88.